Analisis Penyerapan Anggaran Operasional dan Pemeliharaan Kantor di Pengadilan Negeri Semarang Kelas IA Khusus - Salma Febriana Danuputri; Sri Nawatmi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the excess realization of operational and office maintenance at the Special Class IA Semarang District Court, with a focus on the causal factors, and how to overcome budget excesses. The research method used is descriptive qualitative with empirical studies at the Special Class IA Semarang District Court. The data collected was RKA-KL (Work Plan and Budget) and LRA (Budget Realization Report) then conducted in-depth interviews after which analysis was carried out to draw conclusions. The results of the research show that several factors that cause excess operational and office maintenance budgets are unrealistic or non-comprehensive budget planning, changes in economic conditions, inefficiencies in project or operational management, lack of control and supervision of expenditure and non-compliance in the implementation of budget policies or lack of coordination. . How to overcome operational budget excesses at the Special Class IA Semarang District Court by strengthening the budget planning process, implementing a strict budget monitoring and control system and increasing the capacity and competence of human resources involved in budget management.